Book Review: D.G. Janelle & D.C. Hodge (eds.) Information, Place and Cyberspace. Issues in Accessibility - Priemus, Hugo (European Journal of Transport and Infrastructure Research, 2001)
Since 1995, Springer Verlag has published the series ‘Advances in Spatial Science’, in which studies have appeared about ‘Sustainable Cities and Energy Policies’ (R. Capello, P. Nijkamp & G. Pepping), Geographical Information and Planning (J. Stillwell, S. Geertman & S. Openshaw, eds.) and ‘Spatial Dynamics of European Integration’ (H.M. Fischer & P. Nijkamp, eds.) and so forth. In 2000, the book ‘Information, Place and Cyberspace. Issues in Accessibility’ appeared, published by Don Janelle and David Hodge. The book was a consequence of a workshop in the context of the Varenius project and funded by the National Science Foundation, held in November 1998 in Pacific Grove (California). The theme of the conference was ‘Measuring and Representing Accessibility in the Information Age’. It was sponsored by the National Center for Geographic Information and Analysis (NCGIA). The objectives of the book are to broaden understanding of conceptual and analytical approaches to accessibility research appropriate to the information age, and to demonstrate possible contributions for geographic information science in representing the geographies of the information society. In seeking to meet these objectives, the editors and authors highlight significant linkages among information resources, traditional places, and cyberspace, and focus on expanding models of space (and time) that encompass both the physical and virtual worlds